THE ROLE OF EDUCATION IN THE TRANSMISSION OF THE EFFECTS OF MIGRATION REMITTANCES ON THE ECONOMIC GROWTH OF SUB-SAHARAN COUNTRIES - (:unkn) unknown (My University, 2023)
The link established between migratory remittances and the economic development of the origin migrants' countries has long been the subject of several studies, both theoretical and empirical. Essentially supposed to be linear or non-linear of the quadratic type, “migration hump”, this paper demonstrates a new cyclical triangular relationship between Remittances-Education-Growth. The interest of this article is to theoretically discover the axial role that education plays in the transmission of the effects of migratory remittances on the original economy of migrants. The result is the following: remittances from migrants in SSA will only have long-term effects on his economic growth if and only if they would have been directed towards investment in education in the course term. Thus, this paper generates a new theory that we qualify as: “theory of selectivity of uses of remittances”.Keywords: Migrant remittances; Education; Economic growth; triangular causality and sub-Saharan Africa
Keywords: African Research